Workshop Pembuatan Book Chapter Berbasis AI Bagi Guru MGMP Bahasa Inggris SMK Kabupaten Kediri - M. Syaichul Muchyidin; Erwin Hari Kurniawan; Muhammad Saifuddin; Nur Kamilatur (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2026)
This project's community service effort will concentrate on improving the literacy skills of teachers at the MGMP Bahasa Inggris SMK Kabupaten Kediri school by using artificial intelligence to create book chapters as teaching materials. The instruction has been sequential and integrative, starting with assessing the participants' teaching needs through questionnaires and observation, then planning relevant training modules, implementing AI-powered interactive hands-on workshops, and evaluating the participants' outcomes and understanding. The results of the service activity show that teachers' digital literacy skills have improved significantly. For example, 85% of the participants were able to raise book chapters that met academic standards. This shows that teachers are now more creative and innovative when it comes to making teaching materials. This activity not only gave teachers even more creative ideas for making lesson plans, but it also helped with the implementation of the Merdeka Belajar policy and the national digital literacy policy, both of which could make Indonesian high schools' education better in the long term.